1964
DOI: 10.2136/sssaj1964.03615995002800050023x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Liming on Yields and Composition of Heavily Fertilized Grasses and on Soil Properties Under Humid Tropical Conditions

Abstract: Heavily fertilized tropical grasses responded strongly to liming on two typical soils of the Humid Tropics. Liming increased the Ca and decreased the Mn content but did not affect the phosphorus or Mg content of the grasses. Surface applications of limestone were as effective as mixing limestone with the surface soil and one application was as effective as two applications at 2‐year intervals. Exchangeable Al and Mn content of the soils was sharply increased by fertilization alone but was decreased by liming. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…As an alternative comparison, the same solutions were titrated with NaOH to maintain pH 4. First, addition of the salts displaced Al 3+ and allowed for Al phosphate precipitation as expected, but the precipitation reaction caused pH to further decrease because protons are a product of this reaction (Reaction (9)). This inhibited further Al phosphate precipitation.…”
Section: Dynamics Among P Reactions In Soilmentioning
confidence: 74%
See 2 more Smart Citations
“…As an alternative comparison, the same solutions were titrated with NaOH to maintain pH 4. First, addition of the salts displaced Al 3+ and allowed for Al phosphate precipitation as expected, but the precipitation reaction caused pH to further decrease because protons are a product of this reaction (Reaction (9)). This inhibited further Al phosphate precipitation.…”
Section: Dynamics Among P Reactions In Soilmentioning
confidence: 74%
“…Much of the research on basic soil P chemistry was conducted from the 1950s to the 1970s; even at that time there were some contradictory reports. Amarasiri and Olsen [3] commented that "the experimental evidence on the effect of lime on P availability to plants is inconclusive", citing studies that showed that lime increased [4,5], decreased [6,7], or did not change [8,9] plant P concentration. Similarly, in a review that included P by lime interactions, Sumner and Farina [10] showed that there were many inconsistencies in the literature regarding the impact of pH on P uptake.…”
Section: The Need To Consider Context Of Observations and Soil-solutimentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of alkalinity to depth from surface applications or incorporations of lime has been reported previously by several authors (Abruna et al, 1964;Adams and Pearson, 1969). This is eected through the formation of Ca(NO 3 ) 2 in the limed topsoil in the presence of ammonium-based fertilizers and its subsequent leaching to the subsoil where the more rapid rate of assimilation of NO 3 7 over…”
Section: Discussionmentioning
confidence: 66%
“…levels (Ragland and Coleman, 1959;Moschler et al, 1960;Shoop et al, 1961: Abruna et al, 1964. However, it is impossible to deduce from these reports a single common expression for the relationship between plant growth and exchangeable AP+.…”
mentioning
confidence: 99%